Risk Factors and Rates of Hepatitis B Virus Infection among Municipal Waste Management Workers and Scavengers in Ilorin, Kwara State, Nigeria - Henry O. Sawyerr; Rauf O. Yusuf; Adedotun T. Adeolu (Journal of Health and Pollution, 2016)
Background. Poor municipal waste management, including waste treatment and disposal methods, threatens the environment and public health in most developing countries. Lack of proper municipal waste segregation and transportation techniques has increased the potential for the transmission of pathogens such as hepatitis B virus (HBV). Objectives. This study addressed issues relating to the potential risk of infectious diseases and prevalence of HBV among municipal waste workers and scavengers in Ilorin metropolis, Nigeria. Methods. A cross-sectional study was conducted among municipal waste management workers and waste scavengers in Ilorin metropolis, Kwara State, Nigeria. A total of 120 respondents were administered questionnaires during the first stage of the study and participated in the second (testing) stage of the study. The prevalence of an HBV infection biological marker, the Australia antigen (HBsAg), and its association with exposure to waste, socio-demographic factors, and history of occupational injuries with sharp objects/needle sticks was examined. Results. The prevalence of HBV infection among municipal waste management workers and waste scavengers was 2.6% and 16.67% respectively, indicating that scavengers were at higher risk of HBV infection. Conclusions. Lack of proper occupational health safety management among municipal waste management workers was a possible risk factor for HBV infection through injury with sharp instruments. The possible pathway of virus transmission was waste segregation, which is usually carried out with bare hands, and lack of hygiene and occupational safety during waste management activities. Therefore, vaccination against HBV, personal hygiene practices and regular training on occupational safety will help to control risk of HBV infection among municipal waste workers and scavengers. Patient consent. Obtained Ethics approval. Ethical approval was granted from the Kwara State Ministry of Health Ethical Review Committee. Informed consent was obtained from each respondent. Competing Interests. The authors declare no competing financial interests.